Ethylene Role in Plant Growth, Development and Senescence: Interaction with Other Phytohormones - Iqbal, Noushina; Khan, Nafees A.; Ferrante, Antonio; Trivellini, Alice; Francini, Alessandra; Khan, M. I. R. (Frontiers in Plant Science, 2017)
The complex transition, from juvenile to maturity stage, plant life cycle includes growth, reproduction, and senescence of its fundamental organs: leaves, flowers, and fruits. Growth and senescence of leaves, flowers, and fruits involve several genetic networks where phytohormone ethylene plays along with its interaction with other hormones, a key role integrating different signals, allowing the onset of conditions favorable for stage progression, reproductive success and determining how long these organs will live. Changes in ethylene level, its perception, and the hormonal crosstalk directly or indirectly regulate the lifespan of plants. The present review focused on ethylene's role in the development and senescence processes in leaves, flowers and fruits, paying special attention to the complex networks of ethylene crosstalk with other hormones. Moreover, the aspects with limited information have been highlighted for future research. Such information would be useful to extend this study’s understanding regarding the importance of the ethylene role in growth and senescence and help to design future research areas with the aim to improving the qualitative and quantitative traits of crops.